SYNTHESIS AND COMPLETE NMR SPECTRAL ASSIGNMENTS OF NEW BENZYLAMINO COUMARIN DERIVATIVE - Dekić, Vidoslav; Radulović, Niko; Ristić, Milenko; Dekić, Biljana; Ristić, Novica (Bulletin of Natural Sciences Research, 2020)
This research involves the reaction of 4-chloro-3-nitrocoumarin and (4-methoxyphenyl)methanamine, whereby a novel coumarin derivative 4-[(4-methoxybenzyl) amino]-3-nitro-2H-chromen-2-one was obtained in good yield. The reaction was carried out in ethyl acetate, in the presence of triethylamine. Also, a detailed spectral analysis of a new coumarin derivative is presented. Resonance assignment was achieved using one- (1H NMR and 13C NMR) and two-dimensional NMR techniques (1H-1H-COSY, NOESY, HSQC, and HMBC). The NOESY correlations of protons from arylamino substituent and coumarin core indicate their spatial orientation.
Keywords: Coumarins; Synthesis; Spectral analysis; 1H NMR; 13C NMR; 2D NMR